Post-Thaw Morphological Changes in Animal Erythrocytes - Denisova, O. N.; Kuleshova, L. G.; Zemlyanskikh, N. G.; Babijchuk, L. A.; Zhegunov, G. F. (Problems of Cryobiology and Cryomedicine, 2007)
Morphological changes in equine, bovine, and canine erythrocytes, when interacting with 20% dimethylsulfoxide (DMSO) and 30% polyethylene oxide with molecular mass of 1500 (PEO-1500) solutions, as well as after cell cryopreservation at the presence of the mentioned cryoprotectants have been studied in this research using light microscopy. Frozen-thawed erythrocytes of all animal species were established to be transformed into echinocytes under DMSO penetrative cryoprotectant effect and into stomatocytes under a non-penetrative one. The state of animal frozen-thawed erythrocytes when transferring them into physiological conditions was analysed.